Tracing the Linkage of Several Unified Modelling Language Diagrams in Software Modelling Based on Best Practices - Sa’adillah Maylawati, Dian; Ali Ramdhani, Muhammad; Syakur Amin, Abdusy (International Journal of Engineering and Technology, 2018)
Designing software aims to ensure that the systems will be developed truly reflects the needs of users. To ensure the software and the needs of users requires designing software with a good methodology, which can capture a wide range of user needs properly and accurately. One method of designing software is applied through the implementation of Unified Modeling Language (UML) concept. The objective of this article is to reveal the general system and concept of object-oriented software design with UML. The methodology used in writing articles using literature reviews as the primary source of analysis object oriented software design with UML The method that used in this article is literature review as a major source of object-oriented software design analysis with UML. In the next phase, the main topic of the article is clarified, validated, and verified by the model of the Focus Group Discussion. The respondents of this study are informatics lecturers at UIN Sunan Gunung Djati Bandung. This article describes the approach of object oriented software designing with UML, especially how to use use-case, class, and sequence diagram well with the right linkage. And also, how to trace the linkage between those diagrams thus meet all software requirements. Through a good UML method, the produced software is expected to meet the standards of good software quality, which is able to solve problems quickly and accurately.Â Â